Arabic Learning in Industrial Revolution 4.0: Problems, Opportunities, and Roles - Ahmad Fikri; Abdul Muid; Rosita Ilhami; Norhidayah Norhidayah; Aulia Mustika Ilmiani; Muhammad Ikhlas (Arabic Education Department, Islamic Studies Faculty, Universitas Muhammadiyah Malang, 2021)
Technological capabilities in the era of the industrial revolution 4.0 can facilitate the learning process. However, some Arabic language education students at Jambi University still find it difficult to learn Arabic and decide to change majors. This study finds out how the problems, opportunities, and roles of the Arabic language during the industrial revolution 4.0 in the Arabic language education study program at Jambi University. This research is a descriptive qualitative with data collection techniques: a) observation; b) interviews; and c) documentation. Meanwhile, data analysis techniques include: a) data reduction; b) data presentation; c) conclusions. Triangulation and discussion has been use to validate the data. The results show that: a) the problems of learning Arabic, such as: 1) differences background for the students; 2) students are less interested in learning Arabic; 3) no Arabic speaking environment; and 4) lecturers have not mastered technology; b) opportunities: the ability to speak Arabic provides an opportunity to get or create jobs not only in the education sector, but also in other sectors; while c) the role of Arabic is one of international language, diplomatic communication between countries in various fields, and learning knowledge from original Arabic sources.